Heart Rate Variability Indices as Possible Biomarkers for the Severity of Post-traumatic Stress Disorder Following Pregnancy Loss - de Faria Cardoso, Cláudia; Ohe, Natalia Tiemi; Bader, Yazan; Afify, Nariman; Al-Homedi, Zahrah; Alwedami, Salma Malalla; O'Sullivan, Siobhán; Campos, Luciana Aparecida; Baltatu, Ovidiu Constantin (Frontiers in Psychiatry, 2022)
Background: Psychological distress, such as posttraumatic stress disorder (PTSD), is commonly evaluated using subjective questionnaires, a method prone to self-report bias. The study's working hypothesis was that levels of autonomic dysfunction determined by heart rate variability (HRV) measures are associated with the severity of PTSD in women following pregnancy loss. Methods: This was an observational prospective cohort study with 53 patients enrolled. The DSM-5 (Diagnostic and Statistical Manual of Mental Disorders) PTSD scale (PCL-5) was used to assess the severity of PTSD in women after pregnancy loss. The cardiac autonomic function was assessed using HRV measurements during a deep breathing test using an HRV scanner system with wireless ECG enabling real-time data analysis and visualization. HRV measures were: standard deviation (SD) of normal R-R wave intervals [SDNN, ms], square root of the mean of the sum of the squares of differences between adjacent normal R wave intervals [RMSSD, ms], the number of all R-R intervals in which the change in consecutive normal sinus intervals exceeds 50 milliseconds divided by the total number of R-R intervals measured (pNN50 = (NN50/n-1)*100%) [pNN50%]. Results: The PCL-5 scores had a statistically significant association with HRV indices (SDNN; RMSSD, and pNN50%. Patients with PTSD had similar mean heart rate values as compared to patients without PTSD (PCL-5), but significantly higher SDNN (median[IQR, interquartile range]: 90.1 [69.1 – 112.1] vs. 52.5 [36.8 – 65.6]), RMSSD (59.4 [37.5 – 74.9] vs. 31.9 [19.3 – 44.0]), and PNN50% values (25.7 [16.4 – 37.7] vs. 10.6 [1.5 – 21.9]). The SDNN of the deep breathing test HRV was effective at distinguishing between patients with PTSD and those without, with an AUC = 0.83 +/- 0.06 (95 % CI 0.94, p=0.0001) of the ROC model. Conclusions: In this study, HRV indices as biomarkers of cardiac dysautonomia were found to be significantly related to the severity of PTSD symptoms in women after pregnancy loss.